PENINGKATAN KEMAHIRAN BAHASA INGGRIS MELALUI PEMBELAJARAN KOSAKATA UNTUK ANAK-ANAK SD DI DESA SETIALAKSANA - Khasanah, Putri Uswatun; Prihhartini, Sya’baningrum; Irham, Irham (Universitas Islam 45 Bekasi, 2023)
This article is written to report the result of the writer’s Community Service Program. There are many elementary schools in Desa Setialaksana that does not make English Language a mandatory subject in their school. Whereas in reality, the importance of the English language as the standard language in many sectors has made it necessary for people to learn it especially from a younger age. To handle this situation, a short educational program was made to introduce the English language to the children in Desa Setialaksana. The target of this program was the 3rd grade students in SD Negeri Setialaksana 02. The program itself was held three times over the course of two weeks, during which the children learned basic English vocabulary and engaged in various games to hold their interest. Through this program, the students got to acquire some new basic English vocabularies which helped in introducing them to the English language. The program was able to reach its goal for the students became interested to learn the English language.